Experimental investigation of electromagnetic GAMs under the influence of 3D magnetic topological structure in EAST. (1st May 2022) - Qu, H; Kong, D F; Xu, M; Liu, A D; Liang, Y F; Zhang, S B; Cai, H S; Qiu, Z Y; Chen, W; Shi, T H; Gu, S; Duan, Y M; et al.
Abstract: The relationship between geodesic acoustic modes (GAMs) and tearing modes (TMs), or locked modes (LMs), have been investigated in EAST. Firstly, multi-branch electromagnetic GAMs are observed synchronously after the excitation of TMs. Broadened radial coverage is observed for these branches, and these frequencies can be described by the dispersion relation of GAM. Secondly, multi-branch electromagnetic GAMs are generated after the excitation of LMs. The toroidal asymmetric structure of GAMs is excited due to the existence of 3D intrinsic error fields, and the radial distribution of those branches is altered accordingly. Four branches of electromagnetic GAMs are observed in the region that is closer to the 'X'-point of the locked magnetic islands, which should be merged into two branches for the region that is closer to the 'O'-point, as confirmed by XUV array measurement. Thirdly, a similar phenomenon is reproduced by the modulation of resonant magnetic perturbation (RMP). The frequency of GAM increases with the current of the RMP coils, and multi-branches of similar modes are generated when the current achieves I R M P = 2.5 kA, where the electrostatic and electromagnetic components are altered accordingly. The features of those branches are modulated by the rotation of the RMP. Therefore, the structures of the pair of GAMs can be different, which should be influenced by the different magnetic topological structure.